Pengaruh Pemanasan pada Aktivitas Antioksidan Ekstrak Etanol Beberapa Varietas Ubi Jalar (Ipomea batatas L) - Umar Santoso; Ellik Setyaningsih; Muhammad Nur Cahyanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
The objectives of the study were to examine antioxidant activity of ethanol extracts of different varieties of sweet potato and the effect of heating on the antioxidant activity of the extracts. The varieties of sweet potato used were Cilembu, Tambakromo, and Gunung Kawi. After the peel was separated from its flesh, each fraction was dried, grounded and extracted with ethanol. Total phenol was analyzed with Folin-Ciocalteu reagent using gallic acid as a standard. Sweet potato ethanolic extracts were made into three concentrations at 100, 150, and 200 ppm in ethanol. Antioxidant activity was determined by DPPH radical scavenging method. Ethanolic extracts of sweet potato flesh and peel were heated at 100 °C for 20, 30, and 40 minutes to examine the effect of heating on the antioxidant activity. All ethanolic extracts of sweet potato exhibited antioxidant activity. There was no difference in antioxidant activity between ethanolic extracts of Cilembu, Tambakromo and Gunung Kawi varieties. Antioxidant activity of the peel extract was higher than that of the flesh for all varieties. In general, antioxidant activity increased as the concentration of the peel extract increased. Heating at 100 °C for 20 and 30 minutes increased the antioxidant activity of the extract, but decreased after heating for 40 minutes.